Kausalitas Mental Accounting dan Pengambilan Keputusan Investasi Mesin Produksi: Suatu Studi Eksperimen - Fadlil Abdani; Fajar Nurdin (Akuntabilitas, 2019)
This research is included in the true experiment which aims to test the main effect and the interaction effect of mental accounting and self efficacy on investment decisions on production machinery. The method used is the true experiment, with the design of 2 x 2 between subjects that uses two levels of mental accounting (existing or absent) and two levels of self efficacy (high or low). Statistical tests are used with ANOVA, for the first and second hypotheses using One Way Analysis of Variance and for the third hypothesis using Two Way Analysis of Variance. The results of the study found that mental accounting proved to influence the investment decision making of production machinery. Self efficacy is also proven to have an effect on investment decisions in production machinery. While the interaction effect between mental accounting and self efficacy does not affect the investment decision making of a production machine.